СПЕЦІАЛІЗАЦІЯ “ДИЗАЙН РЕКЛАМИ" У СИСТЕМІ ВИЩОГО ПЕДАГОГІЧНОГО НАВЧАЛЬНОГО ЗАКЛАДУ (Педагогіка вищої та середньої школи, 2009)
In article Is considered the questions of the role and place of the disciplines "Design of advertisement" in the learning process of the art-graphic department of Kriviy Rig pedagogical university.